OECD/G20 PILLAR TWO: IS IT A COMPATIBLE AND FEASIBLE SOLUTION? - Vita Apriliasari (Politeknik Keuangan Negara STAN, 2021)
This study aims to contribute to the continuing discussion about the compatibility and feasibility of the OECD/G20 Pillar Two measures as a solution to address the remaining base erosion and profit-shifting (BEPS) issues. One triggering such a discussion is the significance of Pillar Two for developing countries. In so doing, a literature review is conducted to gain relevant considerations to the Pillar Two implementation. The analysis lead to the comprehension of the issues surrounding Pillar Two, i.e. justification, complicated design, fairness issues, and effectiveness.